Nghiên cứu ảnh hưởng ức chế của curcumin từ nghệ Curcuma longa tới hoạt tính của Phospholipaza A2, enzym tách ra từ nọc rắn hổ mang (Naja naja) - Toại và cộng sự, Trần Đình (Vietnam Journal of Chemistry, 2014)
Studies on the inhibition of curcumin from Curcuma longa on phospholipase A2 from cobra venom (Naja naja) were carried out. The phospholipase was fractionated by ion-exchange chromatography on a CM-cellulose column (10 x 60 mm) following chromatography on a superdex G-75 column (16 x 90 mm) and its biochemical properties were studied accurately. The phospholipid’s hydrolysis catalyzed by phospholipase A2 has been inhibited by curcumine from Curcuma longa. It seems that, the phospholipase A2 inhibition is following the purely competitive mechanism. The constant of phospholipide hydrolysis KI and inhibition constant k2 have been calculated:  KI = 5.8´10-4 M, k2 = 0,21.10-3.s-1.